BURIALS WITH KNIFE-SHAPED BLADES FROM THE DON REGION AND THE NORTH CAUCASUS - Il'ukov, Leonid Sergeevic; Mel'nikov, Andrej Ur'evic (History, Archeology and Ethnography of the Caucasus, 2022)
In the steppes of Eastern Europe, a whole series of burials were uncovered in simple pits, in which the deceased were buried on their backs, with their legs tucked up, knees up. Their outstretched or half-bent arms lay along the body, hands near the hips, sometimes in the groin area. A flint knife-shaped blade was also discovered there. The bones were richly dyed with ochre. The buried from the Lukovsky I burial ground in the Mozdok district of the Republic of North Ossetia-Alania, explored in 2017 by the archaeological expedition of LLC “OKN-Proekt” (Rostov-on-Don) complements this series of burials, which S.N. Korenevsky attributes to the proto-Yamna period. The use of knife-shaped blades in the funeral rite is not limited to the framework of the Eneolithic period. They are also found in the burials of the Middle Bronze Age. Since this sample group is characterized by the position of the deceased in simple grave pits, it is questionable to include in it undercut and catacomb structures, in which archaic elements of the funeral rite and grave goods are found. A flint knife with a leather handle was not only a “meat knife”, but also a tool for performing surgical operations. It was used to perform operations to apply cuts (tattoos) to the surface of the skin, as well as to perform rituals associated with phallic cults that emerged in a patriarchal society, where the role of men increased. The placement of a flint blade between the thighs, in the groin area, between the palms, suggests its simbolic meaning. A flint blade was used in performing circumcision of the foreskin, in cult sacrifice.
Keywords: Eneolithic-Early Bronze Age; proto-Yamna culture; rectangular pit; knife-shaped blade; flint blade – tool for surgical operations